THE EFFECT OF ALPHA LIPOIC ACID ON BLASTOCYST EMBRYO DEVELOPMENT IN VIVO IN MICE (Mus musculus) EXPOSED CIGARETTE SMOKE - Syahruddin Said; Adi Setyawan Prianto; Senri Utama Pramadipta (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
This study was conducted to find out effect of alpha lipoic acid (ALA) on the development of in vivo blastocyst embryo in mice (Mus musculus) exposed in cigarettes smoke. This study used 30 mice divided into 6 treatment groups factorial 2x3. Factor A is treatment of ALA (0; 16.5 μM; 49.5 μM) per orally. Factor B is the treatment of cigarette smoke (with and without cigarette smoke). Giving cigarette smoke was done by covering the cage with plastic having two holes for cigarette smoke and airflow. The data obtained were analyzed using a complete randomized design (RAL) 2x3, followed by parametric Analysis of Variance (ANOVA) and independent sample T-Test, and Post Hoc Duncan test. The development of embryo of mice reaching blastocyst stage at ALA with dose 16,5 μM (16.00±7.12) were significantly higher (p<0.05) than negative control (13.50±1.73), but no significant effect with ALA dose 49.5 μM (19.25±4.03). The development of mice blastocyst embryos exposed to cigarette smoke (7.25±2.99) were significantly lower (p<0.05) compared with negative control. When the mice exposed to cigarette smoke were given ALA, the development of the blastocyst embryo returned to normal as in control, where the doses of 16.5 μM and 49.5 μM were not significantly different. It can be concluded that (1) ALA dose 16.5 μM and 49.5 μM have positive effect on blastocyst development in vivo, (2) cigarette smoke have negative effect on blastocyst development, (3) ALA 16.5 μM and 49.5 μM per orally capable counteract the oxidative stress caused by exposure to cigarette smoke.